2019
DOI: 10.1172/jci.insight.126599
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinally persistent cerebrospinal fluid B-cells can resist treatment in multiple sclerosis

Abstract: and reports equity in Roche and income as full-time employee.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
2
21
2
Order By: Relevance
“…This is consistent with a highly stable humoral immune response in the CSF of MS patients and underscores that finite samples of CSF cells only represent a small proportion of the IgG-producing B lineage cells in the CNS. The results corroborate early observations of stable OCB patterns on electrophoretic gels (Walsh and Tourtellotte, 1986), and shed new light on previous and contemporary studies detecting a limited overlap in B lineage cell samples collected at different time points (Colombo et al, 2003, Greenfield et al, 2019.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with a highly stable humoral immune response in the CSF of MS patients and underscores that finite samples of CSF cells only represent a small proportion of the IgG-producing B lineage cells in the CNS. The results corroborate early observations of stable OCB patterns on electrophoretic gels (Walsh and Tourtellotte, 1986), and shed new light on previous and contemporary studies detecting a limited overlap in B lineage cell samples collected at different time points (Colombo et al, 2003, Greenfield et al, 2019.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have shown that in MS identical B‐cell clones are present in both the periphery and CNS . That these B‐cell populations further undergo somatic hypermutation in the brain implies the presence of functional germinal centers within the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…B cells are one of the main contributors to chronic autoimmune pathology in multiple sclerosis (MS), as supported by results from large genome‐wide association studies . B‐cell repertoires in the central nervous system (CNS) and the periphery are closely connected, suggesting that disease‐relevant B‐cell networks interact at both sides of the blood–brain barrier . There is evidence that the beneficial effects of anti‐CD20 monoclonal antibody therapy are related to the ablation of functional B cells interacting with T cells .…”
mentioning
confidence: 99%
“…Fresh whole CSF and blood lymphocytes were labeled with the following antibodies: CD3, CD19, CD27, CD38, CD138, and IgD. Using a Beckman MoFlo Astrios cell sorter, CSF and blood B cell subsets were sorted directly into lysis buffer as previously described ( 17 , 31 ): naïve B cells (N; CD19+IgD+CD27–), unswitched memory B cells (USM; CD19+IgD+CD27+), switched memory B cells (SM; CD19+IgD–CD27+), double-negative B cells (DN; CD19+IgD–CD27–), CSF plasmablast/plasma cells (CD19+IgD–CD27hi), and blood plasmablast/plasma cells (CD19+IgD–CD27hiCD38hi) ( Dataset S1 C ). These distinct B cell populations represent classic B cell subsets, as described previously ( 17 , 32 34 ).…”
Section: Methodsmentioning
confidence: 99%